Demokrasi dan Politik Biaya Tinggi (High Cost Politics) - Ahmad Burhan Hakim; Muhyidin Muhyidin (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
Democracy is a concept of state and politics which is considered the most ideal today. Democracy also has an important role in arranging the rules of the political and state game in Indonesia. So that after the 1998 reformation democracy became one of the important ideologies in Indonesian politics. The concepts of justice, openness, representation, transparency and accountability are a series of epic concepts in democracy. The basic concept is actually very noble. However, in practice, democracy is not just a raw concept. Electoral political events have resulted in a logical consequence, namely high-cost politics that cannot be separated from every moment of democracy. So do not be surprised if in political moments such as the Presidential Election, Legislative Member Election, Regional Head Election from Province to Regency and City and even Village Head Election requires large funds. Both in terms of implementation to the succession of candidates. The result is a widespread culture of corruption that occurs in our country. So this will certainly affect state politics in Indonesia. Democracy does have an extraordinary ideal concept, but the implementation of democracy requires a lot of funds.